Slow getting up : a story of NFL survival from the bottom of the pile - Jackson, Nate. (New York : Harper Perenial, 2014)
"One man's odyssey into the brutal hive of the National Football League. This is not a celebrity tell-all of professional sports. Slow Getting Up is a survivor's real-time account of playing six seasons (twice as long as the average NFL career) for the San Francisco 49ers and the Denver Broncos. As an unsigned free agent who rose through the practice squad to the starting lineup, Nate Jackson is the talented embodiment of the everyday freak athlete in professional football, one of thousands whose names go unmentioned in the daily press. Through his story recounted here-- from scouting combines to preseason cuts to byzantine film studies to glorious touchdown catches-- even knowledgeable football fans will glean a new, starkly humanized understanding of the daily rigors and unceasing violence of quotidian life in the NFL. Fast-paced, lyrical, and hilariously unvarnished, Slow Getting Up is an unforgettable look at the real lives of America's best twenty-year-old athletes putting their bodies and minds through hell"--From publisher's web site.
Prologue: Goodbye, dude (2008) -- The first seven years (2002) -- My life as Randy Moss (2003) -- Nein lives (2004) -- Grid-irony (2004) -- Meat sacks (2005) -- Plummer's crack (2006) -- Pointy balls (2007) -- Farewell, Bronco Betty (2007) -- Rocky Mountain high (2007) -- Watermelon seeds (2007-2008) -- The last dislocation (2008) -- The after affect (2009) -- Epilogue: The flood (2014).
This paperback edition contains a new bonus chapter.
Keywords: Jackson, Nate; Football players -- United States -- Biography